Structural characterization of (Sm, Tb)PO4 solid solutions and pressure-induced phase transitions. Issue 11 (September 2018) - Heuser, J.M.; Palomares, R.I.; Bauer, J.D.; Rodriguez, M.J. Lozano; Cooper, J.; Lang, M.; Scheinost, A.C.; Schlenz, H.; Winkler, B.; Bosbach, D.; Neumeier, S.; Deissmann, G.
Abstract: Sm1- x Tb x PO4 solid solutions were synthesized and extensively characterized by powder X-ray diffraction, vibrational spectroscopy, and X-ray absorption spectroscopy. At ambient conditions solid solutions up to x = 0.75 crystallize in the monazite structure, whereas TbPO4 is isostructural to xenotime. For x = 0.8 a mixture of both polymorphs was obtained. Moreover, a phase with anhydrite structure was observed coexisting with xenotime, which was formed due to mechanical stress. Selected solid solutions were investigated at pressures up to ∼40 GPa using in situ high pressure synchrotron X-ray diffraction and in situ high pressure Raman spectroscopy. SmPO4 and Sm0.5 Tb0.5 PO4 monazites are (meta)stable up to the highest pressures studied here. TbPO4 xenotime was found to transform into the monazite structure at a pressure of about 10 GPa. The transformation of Sm0.2 Tb0.8 PO4 xenotime into the monazite polymorph commences already at about 3 GPa. This study describes the reversibility of the pressure-induced (Sm, Tb)PO4 xenotime-monazite transformation.